Assessing the role of local councils in the development of sustainable urban security (Case Study; Urmia City) - Parvin Daneshvar; Taghiloo Ali Akbar; Hassan heydari (تحقیقات کاربردی علوم جغرافیایی)
Increasing urbanization today and the lack of integrated urban management have led to inadequate planning in cities. In this regard, the local councils, as the most prominent local institutions and the most important decentralization manifestations, symbolize the serious presence of the people to determine their own fate, if they are institutionalized in the governance structure as coordinators of the executive agencies. In these cities, they can play a valuable role in the social security of cities. The present study was conducted using descriptive-analytical approach and field method. In this study 354 people were selected using Cochran model. Next, based on the results of the questionnaire, the results were analyzed using SPSS software. Conclusions: Based on the Friedman test, among the research items, the second item is "Social Security Development", and the first item is "Economic Security Development". Among the items, the second item (Social Security) with 2.90 points out that the role of local councils in social security development is higher than other dimensions and the first item with 1.98 points of economic security development comes in last. has taken. Also, the one-sample t-test showed that the significance level of the test is less than (0.05) and at 95% confidence level there is a positive significant difference between the dimensions of council functions and the dimensions of sustainable urban security development.